Analisis Penggunaan Media Pembelajaran di Sekolah Dasar - Kiki Rizqyatul Ummah (Jurnal DIDIKA: Wahana Ilmiah Pendidikan Dasar, 2023)
21st century learning is learning that is no longer teacher-centered. learning in this century emphasizes learner-centered learning, so this is a demand for teachers to create fun learning and provide stimulus so that students can be active in the classroom. This research aims to find out the learning process at the school, how the teacher teaches, the use of learning media, and the condition of students when learning takes place. This research uses a qualitative approach and descriptive method. Descriptive qualitative research interprets the data concerned with the situation that is happening which in this context is about the use of media in the learning process at SDN Teras 3. The results of the analysis show that the use of learning media at SDN Teras 3, especially in class IV, is lacking. Keywords: Learning, 21st Century, Media.